A Time and Place for Language Comprehension: Mapping the N400 and the P600 to a Minimal Cortical Network - Harm eBrouwer; John C. J. Hoeks (Frontiers in Human Neuroscience, 2013)
We propose a new functional-anatomical mapping of the N400 and the P600 toa minimal cortical network for language comprehension. Our work is anexample of a recent research strategy in cognitive neuroscience, whereresearchers attempt to align data regarding the nature and time-course ofcognitive processing (from ERPs) with data on the cortical organizationunderlying it (from fMRI). The success of this `alignment' approachcritically depends on the functional interpretation of relevant ERPcomponents. Models of language processing that have been proposed thus fardo not agree on these interpretations, and present a variety of complicatedfunctional architectures. We put forward a very basic functional-anatomicalmapping based on the recently developed Retrieval-Integration account oflanguage comprehension (Brouwer, Fitz, & Hoeks, 2012). In this mapping, the leftposterior part of the Middle Temporal Gyrus (BA 21) serves as anepicenter (or hub) in a neurocognitive network for theretrieval of word meaning, the ease of which is reflected in N400 amplitude.The left Inferior Frontal Gyrus (BA 44/45/47), in turn, serves a networkepicenter for the integration of this retrieved meaning with the word'spreceding context, into a mental representation of what is beingcommunicated; these semantic and pragmatic integrative processes arereflected in P600 amplitude. We propose that our mapping describes the coreof the language comprehension network, a view that is parsimonious, hasbroad empirical coverage, and can serve as the starting point for a morefocused investigation into the coupling of brain anatomy andelectrophysiology.